Real time monitoring system for elderly - Wong, Jo Yeng (2024)
This research improved aged care technology by developing a real-time tracking system to detect falls and track elderly people. This was accomplished using Raspberry Pi and GPS technologies. It prioritized the safety, well-being and autonomy of elderly especially those living alone or in assisted living facilities. The initiative attempted to address common issues like falls, wandering and confusion among senior persons with conditions like dementia or reduced mobility. A Raspberry Pi controlled the system together with a GPS module for accurate location monitoring and fall sensors. A thorough analysis of aged care needs and challenges is used. We designed and developed hardware and software throughout the analysis. These solutions have user-friendly carers interfaces and rapid alerts and notifications and were extensively tested in real life. The project combined accurate real-time tracking and fall detection, allowing caretakers to quickly respond to occurrences and improve elderly safety. To ensure efficiency, precision and security, the system was validated. Thus, it has become an affordable and unique elderly care technology option. This project is notable for using Raspberry Pi, GPS and advanced fall detection algorithms for accurate tracking. Software was developed using the Geany IDE for versatility and seamless integration in numerous care scenarios. This initiative provided an innovative way to improve elderly adults' safety, autonomy and involvement in care environments.